1980
DOI: 10.1177/014616728064008
|View full text |Cite
|
Sign up to set email alerts
|

A Molar Approach to Social Knowing

Abstract: Exemplary research in social cognition and perception is examined. It is suggested that a singular focus on internal, intraindividual cognitive and perceptual processes is not sufficiently broad to account adequately for the spectrum of social knowing phenomena. A more molar approach to social knowing than can be found in contemporary work in social cognition and perception is advocated. More specifically, it is suggested that work on molecular cognitive and perceptual processes will help elucidate basic socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This type of analysis reflects an ecological approach to social knowing. Inspired by the work of J.J. Gibson in object perception [13,14], several theorists have suggested that much of the important activity in social understanding occurs immediately during perception [15][16][17][18][19][20][21][22][23][24][25][26], rather than as the result of complex inferential activity, however automated [27]. Even Fiske and Taylor [27] succinctly argued in support of the ecological approach by advancing that:…”
Section: Introductionmentioning
confidence: 99%
“…This type of analysis reflects an ecological approach to social knowing. Inspired by the work of J.J. Gibson in object perception [13,14], several theorists have suggested that much of the important activity in social understanding occurs immediately during perception [15][16][17][18][19][20][21][22][23][24][25][26], rather than as the result of complex inferential activity, however automated [27]. Even Fiske and Taylor [27] succinctly argued in support of the ecological approach by advancing that:…”
Section: Introductionmentioning
confidence: 99%